Transformation of Religious Moderation Values ​​in a Multicultural Society: A Study of Islamic Education Approaches in North Bengkulu Regency - Panca Oktoberi; Abdur Rahim; Ahmad Siddiq Ridha (UIN Fatmawati Sukarno Bengkulu, 2026)
Background: Indonesia, as a multicultural country, faces challenges of intolerance and radicalism that threaten social stability. North Bengkulu Regency, as a multicultural area, requires religious moderation strengthening strategies to maintain harmony among religious communities.Methods: This study employed a qualitative approach using case study method. Data were collected through in-depth interviews, participatory observation, and documentation studies on the religious moderation strengthening program. Program evaluation utilized Ralph W. Tyler's model emphasizing planning, implementation, and outcomes aspects.Results: The program was implemented through the establishment of the Interfaith Religious Representatives Forum (FPUB), interfaith dialogue, communal work across religious groups, harmony camps, harmony parades, and moderation training. Five main supporting factors were identified: active roles of formal institutions, clear planning documents, open social conditions, involvement of religious leaders, and systematic program logic. Inhibiting factors included limited budget, restricted community understanding, and minimal competent human resources.Conclusion: The religious moderation strengthening program in North Bengkulu Regency successfully internalized moderate Islamic values through participatory community-based education approaches. The program implementation demonstrated strong alignment with Islamic education principles, particularly wasathiyah values, tolerance, and social justice in multicultural society contexts.